E-PORTFOLIO AS A MEANS OF UPGRADING PROFESSIONAL COMPETENCE OF PEDAGOGICAL STAFF FROM HIGHER EDUCATIONAL INSTITUTIONS - Isomov, Ismoil; Shoymardonov, Tuymurod; Obidov, Azamat (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article discusses the use of an electronic portfolio system in the development of professional competence of pedagogical staff. The effectiveness of electronic monitoring system in the management of a portfolio of teaching staff’s professional activity and the popularization of pedagogical experiments are revealed. Besides, examples of overseas best practices are provided.